The Nearctic species Margarinotus (Ptomister) immunis (Erichson, 1834) discovered in Slovakia (Coleoptera: Histeridae) - Lackner, Tomáš; Mazur, Sławomir (Zootaxa, 2015)
The species Margarinotus (Ptomister) immunis (Fig. 1) was described by Erichson in 1834 as Hister immunis. Erichson (1834: 143) stated its type locality as “Nordamerika” and this species has been always treated exclusively as an element of the Nearctic fauna (see e.g. Mazur 1997, Bousquet & Laplante 2006 or Mazur 2011). Bousquet & Laplante (2006: 317) state that it inhabits eastern North America from Prince Edward Island and Nova Scotia to the Ontario Peninsula, southern Manitoba, and Saskatchewan, south to Florida and that the provincial record of British Columbia given by Davies (1991: 139) is likely erroneous. According to Bousquet & Laplante (2006: 317) the species M. (P.) immunis is normally found in forest litter and on carrion.